Continuous-discontinuous sheet moulding compounds – Effect of hybridisation on mechanical material properties. (15th October 2018) - Trauth, Anna; Weidenmann, Kay André
Abstract: Discontinuous fibre reinforced polymers offer a high design freedom to manufacture parts with complex geometries, but due to the finite fibre length and fibre orientation, mechanical performance is limited. To overcome this drawback continuous-discontinuous sheet moulding compounds (CoDicoSMC) aim to combine the advantages of discontinuous, chopped glass fibre reinforced as well as unidirectional, continuous carbon fibre reinforced composites. An adopted SMC process allowing for the manufacturing of continuous carbon fibre reinforced SMC was successfully implemented. The hybrid SMC was combined in a one-shot compression moulding process. Hybridisation of SMC enhanced mechanical material properties with a significant increase in tensile (+171%) and compressive (+151%) moduli of elasticity and tensile strength (+204%). The resulting stiffness of the laminate can be described by a modified rule of mixtures. Damage is characterized by a progressive failure of the continuous carbon fibre layers, due to interfibre fractures and fibre breakage, followed by interlaminar delamination and failure of the discontinuous phase.